Faktor-Faktor Yang Mempengaruhi Produksi Budidaya Rumput Laut Di Kabupaten Pekalongan Provinsi Jawa Tengah - Wijianto Wijianto; Irzal Effendi; Iis Diatin; Tatag Budidardi; Yani Hadiroseyani (Universitas Mataram, 2024)
Seaweed is a fishery product that is widely used in various industries, including food, cosmetics, feed and others. Seaweed production does not always increase according to the target but there are several declines, such as in Pekalongan Regency in 2018, there was a quite drastic decline compared to the previous year. The aim of this research is to analyze the factors that are thought to have caused a decline in seaweed production in Central Java Province, especially in Pekalongan Regency. The research method used in the research is secondary data obtained from the Pekalongan Regency Central Statistics Agency. The results of the analysis that have been carried out show that there are several factors that have caused the decline, including tidal waves that occurred in 2017-2018, a decrease in the number of ponds owned by the community, and an erosion rate that is estimated to occur at 0.5 m per year. Decline in seaweed production in Pekalongan Regency is caused by several factors including abrasion, tidal waves, and a decrease in the number of ponds owned by the community in the Pekalongan Regency.